(untitled) (Pedagogy of Higher and Secondary Education, 2006)
In article evolution of the contents and methods of teaching of disciplines of a graphic cycle in system of school education of Ukraine on extent XIX - the beginnings of XX century is traced on the basis of the analysis of normative documents of that epoch.